2011
DOI: 10.3758/s13415-011-0064-8
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms underlying the higher levels of subjective well-being in extraverts: Pleasant bias and unpleasant resistance

Abstract: The present study investigated the neural mechanisms that underlie the higher levels of subjective well-being in extraverts. The impact of extraversion on the human sensitivity to pleasant and unpleasant pictures of diverse emotional intensities was examined. We recorded event-related potentials (ERPs) for highly positive (HP), moderately positive (MP), and neutral stimuli in the pleasant session, and for highly negative (HN), moderately negative (MN), and neutral stimuli in the unpleasant session, while subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 70 publications
7
43
3
Order By: Relevance
“…However, no significant difference was obtained in ambiverts. In support of these findings, a study by Yuan et al (2012), investigating the neural mechanisms behind the subjective well-being in extraverts using pictures of different emotional intensities, found that highly positive (HP) and moderately positive (MP) pictures elicited P3 of higher amplitude in extraverts as compared to ambiverts (43). Given the fact that P3 amplitude reflects the amount of attentional resources invested in processing a given stimulus (12), and also that Johnston, Miller and Burleson (1986) proposed that the P3 amplitude is proportional to the emotional value of the eliciting stimuli, the present study, therefore, found extraverts to allocate more attention to self-related pronouns due to their emotional significance (44).…”
Section: N200 Amplitude and Latencysupporting
confidence: 76%
See 3 more Smart Citations
“…However, no significant difference was obtained in ambiverts. In support of these findings, a study by Yuan et al (2012), investigating the neural mechanisms behind the subjective well-being in extraverts using pictures of different emotional intensities, found that highly positive (HP) and moderately positive (MP) pictures elicited P3 of higher amplitude in extraverts as compared to ambiverts (43). Given the fact that P3 amplitude reflects the amount of attentional resources invested in processing a given stimulus (12), and also that Johnston, Miller and Burleson (1986) proposed that the P3 amplitude is proportional to the emotional value of the eliciting stimuli, the present study, therefore, found extraverts to allocate more attention to self-related pronouns due to their emotional significance (44).…”
Section: N200 Amplitude and Latencysupporting
confidence: 76%
“…Given the fact that P3 amplitude reflects the amount of attentional resources invested in processing a given stimulus (12), and also that Johnston, Miller and Burleson (1986) proposed that the P3 amplitude is proportional to the emotional value of the eliciting stimuli, the present study, therefore, found extraverts to allocate more attention to self-related pronouns due to their emotional significance (44). According to Yuan et al (2012), this can possibly be explained by extraverts' lower threshold for pleasant emotion and higher threshold for unpleasant emotion, while ambiverts have a high threshold for pleasant emotion and a low threshold for unpleasant emotion (43). Extraverts are responsive to emotionally pleasant stimuli irrespective of its emotional valence (30).…”
Section: N200 Amplitude and Latencymentioning
confidence: 77%
See 2 more Smart Citations
“…As a result, an enormous amount of results reveals the wide range of behaviors and consequences related to this trait is available (Wilt & Revelle, 2009). Less research exists in relation to ambiverts (e.g., Grant, 2013;Yuan et al, 2012). Ambiversion was proposed by Eysenck (1971) to characterize individuals that present both extraversion and introversion features and typically present intermediate scores in extraversion scales.…”
Section: Introductionmentioning
confidence: 99%